Contextualizing Work-Integrated Learning in Higher Education: Global Trends and Islamic Education Evaluation - Budi Santoso (International Journal of Multidisciplinary Research of Higher Education, 2026)
The gap between graduates’ competencies and labor market demands has driven the adoption of Work-Integrated Learning as a bridge between academic knowledge and professional practice. Within Indonesia’s Merdeka Belajar Kampus Merdeka policy, the Teaching Assistance Program embodies this approach, yet its integration with Islamic education perspectives remains underexplored. This article discusses global trends in Work-Integrated Learning, evaluates the extent to which the Teaching Assistance Program fulfills essential principles, and proposes a conceptual framework relevant to Islamic higher education. Using a qualitative content analysis of 75 accredited international and national journal articles published between 2020 and 2025, data were examined thematically through Miles and Huberman’s interactive model. Findings reveal three major trends: (1) expansion from workplace-based to non-workplace models; (2) integration into teacher education through teaching practicums; and (3) digitalization in the post-pandemic era. The Teaching Assistance Program substantively aligns with Work-Integrated Learning principles but requires reinforcement in authentic assessment, structured supervision, and pedagogical reflection. The study contributes to competency-based curriculum development for teacher education in Indonesia, offering implications for Islamic higher education in strengthening professional competencies, pedagogical skills, and ethical values rooted in Qur’anic traditions.